Elections in Latin America: The problematic use of a democratic institution - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2009)
In present-day Latin America 'election activism' is widespread. Elections are held with growing frequency and increasingly serve differing aims. In many cases, however, they do not go along with a strengthening of democracy. A current example is Argentina, where early congressional elections were held on June 28 and the government and opposition fought in court over the legality of several candidateships. Argentina thus joined the ranks of countries like Bolivia and Venezuela, where elections not only serve as a source of democratic legitimation and a form of political oversight, but are also used by both ruling parties and opposition forces in certain situations as a means to extend their own power
Keywords: 320